L’évolution des discours parlementaires sur le logement social en France dans les années 2000 - Yankel Fijalkow (Métropoles)
This article aims to identify the evolution of representations of the political world with regard to social housing during the 2000s. To this end, it examines its place in the French real estate context and its integration in the housing policies watch word. Using an analysis of the political discourse, in terms of representation, norms, values and watch words, it analyzes each of the main debates on social housing between 2000 and 2018. The evolution of discourses increasingly values the effectiveness of public investment, the performance of organizations, solidarity between territories, a fair distribution, and indignation for the most bad-housed. They lead to the promotion of the autonomy of the organizations, the broadening of the notion of social housing and the contracting with the State to build more according to the “needs”.